Soil Test Summaries Pinpoint Fertilizer Needs in Bundi District - Sharma, C P; Singh, Harvinder; Seth, S P (Annals of Arid Zone, 2016)
Soil fertility map showing the available nutrient status of Bundi district has been prepared. Soil test summary data. crop acreage and current fertilizer recommendations are used to estimate nutrient needs for Bundi district.